The Afrobeats Digital Diaspora: TikTok, Algorithmic Curation, and the Remaking of Nigerian Cultural Identity in the Global Mainstream (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The global ascent of Afrobeats is often narrated as an organic cultural movement, yet this paper argues that its recent, accelerated proliferation is fundamentally co-constituted by the symbiotic relationship between the Nigerian digital diaspora and the algorithmic architectures of social media platforms, with TikTok as a primary agent. Moving beyond narratives of simple cultural export, this study examines how TikTok’s algorithmic curation—particularly its recommendation engine and format of viral challenges—amplifies, simplifies, and repackages specific sonic and visual tropes of “Naija” identity for global consumption. Employing a conceptual framework rooted in platform studies and diaspora media theory, this paper analyzes how diaspora users act as cultural intermediaries, using Afrobeats to perform and negotiate identity, while simultaneously being guided by the platform’s logic of virality. Through case studies of tracks like “Calm Down” by Rema and “Love Nwantiti” by CKay, and analysis of viral dance challenges, the research demonstrates a feedback loop where algorithmic preference shapes artistic output and diaspora engagement. The findings reveal a tension between authentic cultural expression and a “platformized” Nigerian identity—one that is often flattened, meme-ified, and decontextualized to fit the logics of algorithmic discovery. This research contributes a critical new framework for understanding 21st-century cultural globalization, positioning platform algorithms and user-generated content not as neutral conduits, but as active agents in the construction and circulation of national identity from the Global South.